New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada: Paederinae - Reginald Webster; Ian DeMerchant (ZooKeys, 2012)
We report 17 species of Paederinae new for New Brunswick, Canada. Ten of these species, Lathrobium othioides LeConte, Lathrobium amplipenne Casey, Lathrobium armatum Say, Lathrobium confusum LeConte, Lathrobium debile LeConte, Achenomorphus corticinus (Gravenhorst), Rugilus rufipes Germar, Homaeotarsus bicolor (Gravenhorst), Homaeotharsus cribratus (LeConte), and Homaeotarsus pallipes (Gravenhorst) are newly recorded for the Maritime provinces. This brings the total number of Paederinae recorded from New Brunswick to 36 species. Additional records are presented for the recently reported Lathrobium simile LeConte and Lathrobium washingtoni Casey. Collection and habitat data are presented for all species.